Removal of Copper Ions onto Walnut Shells by Using Batch and Continuous Fluidized Bed (Journal of Engineering, 2013)
An agricultural waste (walnut shell) was undertaken to remove Cu(II) from aqueous solutions in batch and continuous fluidized bed processes. Walnut shell was found to be effective in batch reaching 75.55% at 20 and 200 rpm, when pH of the solution adjusted to 7. The equilibrium was achieved after 6 h of contacting time. The maximum uptake was 11.94mg/g. The isotherm models indicated that the highest determination coefficient belongs to Langmuir model. Cu (II) uptake process in kinetic rate model followed the pseudo-second-order with determination coefficient of 0.9972. More than 95% of the Cu(II) were adsorbed on the walnut shells within 6 h at optimum agitation speed of 800 rpm. The main functional groups responsible for biosorption of Cu(II) onto walnut shell were hydroxyl, carbonyl,carboxylate, carboxylic acids, alcohols groups, and aromatic compounds. In continuous system, fluidized bed column at 20 , and pH 7 was carried out to study the effects of various parameters like (flow rate,bed depth, and initial concentration). The time of breakthrough was 97 min when the initial concentration (Co= 20mg/l), bed depth (L=10cm), and flowrate (Q=10l/h)